What Are the Impacts of Long-Term Vinasse Application on Clayey and Sandy Soils? - Cardoso, Edmilson N’dami Lopes [UNESP]; Coelho, Anderson Prates [UNESP]; Fernandes, Carolina [UNESP] (Springer Nature, 2022)
Long-term vinasse application effects evaluation on the chemical and physical attributes of soils with different textures is fundamental to support waste application recommendation. The aim was to evaluate whether long-term vinasse application changes the chemical and physical attributes of clayey and sandy soils cultivated with sugarcane. The experiment was carried out in two areas in the southeast region of Brazil in soils with sandy (80 g kg−1 clay) and clayey (490 g kg−1 clay) textures. In each soil, there were two sugarcane management conditions, one with vinasse application for more than 10 years and the other without vinasse application. Ten disturbed and undisturbed soil samples were collected in each area in the 0.00–0.10 m, 0.10–0.20 m and 0.20–0.30 m layers to evaluate soil chemical and physical attributes. Due to the dependence structure of the variables, multivariate factor analysis was applied. Vinasse application increased macronutrients content, on average, by 23% in the clayey soil and 80% in the sandy soil. In addition, long-term vinasse application increased the microporosity of the sandy soil by 22%, enabling greater availability of water for sugarcane. Long-term vinasse application is a sustainable management for sugarcane areas, regardless of soil texture, as it increases soil fertility by increasing organic carbon and macronutrient contents and does not generate soil acidification potential.
Keywords: Macronutrients; Oxisol; Quartzipsamment; Soil acidity; Soil structure